AN ANALYTICAL STUDY OF THE ROLE OF THE CENTRAL BANK OF IRAQ IN SUPPORTING AND IMPLEMENTING THE STATE’S GENERAL BUDGET - Sura Rafeeq Abdulalrazaq (Scholar Express Journals, 2025)
This research aims to shed light on the vital role played by the Central Bank of Iraq in supporting and implementing the state's general budget, given the economic and financial challenges facing the country. The research addresses the central bank's core functions, such as managing monetary policy, controlling inflation levels, and supporting the stability of the national currency, and how these functions impact the implementation of the general budget. This research aims to shed light on the vital role played by the Central Bank of Iraq in supporting and implementing the state's general budget, given the economic and financial challenges facing the country. The research addresses the central bank's core functions, such as managing monetary policy, controlling inflation levels, and supporting the stability of the national currency, and how these functions impact the implementation of the general budget.
Keywords: Central Bank of Iraq; general budget; monetary policy